PENGARUH SUPLEMENTASI PAKAN LOKAL PADA INDUK KAMBING BLIGON BUNTING TUA SAMPAI MENYUSUI UNTUK MENEKAN KEMATIAN ANAK YANG DIPELIHARA DI PADANG SABANA TIMOR BARAT - Arnold Manu; Endang Baliarti; Soenaryo Keman; Frans Umbu Datta (Universitas Tadulako, 2007)
The research was conducted in Lili savanna at West Timor. Fifteen Bligon does the late gestation were used for ten weeks.Does were randomly devided into 3 groups of treatment such as, R0 = control, does grazed during daylight ; R1 = R0 + 1 % suplement onbody weight basic ; R2 = R0 + 2 % suplement on body weight basic. The aims of the research were to study the effect of local feedsuplement on bligon does at late gestation period to lactation period to decrease kids mortality grazed at Timor savanna. The result of theresearch shows the birth weight and daily gain, colostrum and blood Ig of the kids and milk production score of group R2 (2.42 kg ;106.15 g ; 94.8 mg/ml; 2,13 g/dl, 630,83 g) were significant higher than (P<0.01) R1 (2.25 kg, 79.33 g, 71.2 mg/ml ; 1.87 g/dl, 516.64g) and R0 (1.73 kg, 47,11 g ; 43 mg/ml ; 0,97 g/dl, 409.55 g) except for the birth weight of R2 and R1. Blood components (PVC,leukocyte, erytrocyte, Hb, glucose, protein) as well as neutrofil phagocytosis R2 were higher than R1 and R0. The conclusion of thisresearch is that local feed suplement can increase health status and decrease Bligon kids mortality whose grazed at Timor Savanna.Keywords : Lactation and gestation does, local feed supplement, savanna, kids mortality.